(untitled) (Bangladesh Journal of Pharmacology, 2023)
Traditional medicine in tropical areas often includes the use of Swietenia mahagoni to treat a wide range of conditions. However, preclinical testing is crucial to ensure their safety profile and address any remaining concerns about their efficacy. The zebrafish model of open field test shows that decreased dopamine and cholinergic transmission causes impaired locomotion and diminished exploratory behavior. In addition to the elevation of 5-HT and GABA reported in the mirror bite test findings, the extract may have suppressed dopamine expression. The mirror-bite test and the light-dark test both showed elevated levels of GABA expression. Findings from the predator avoidance test are very suggestive of a neurotransmitter-regulating action of the extract.